Vocabulary Assessment Strategy of English Teacher in Junior High School - Artha Priscilla S; Fara Fadhila; Febry Sarah A Tampubolon; Erikson Saragih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
In language learning, vocabulary mastery is very important, so a comprehensive language learning strategy is needed. Vocabulary is all words contained in a language, students must know vocabulary to produce a sentence. Vocabulary is also a fundamental element for learning English. Thus, the purpose of the study was to find out whether the strategies and methods that teachers use in junior high school in English learning can improve students' vocabulary or not. The subjects analyzed in the study were English teachers in junior high school. This research uses a qualitative research approach with survey research design in the form of Google forms. Researchers gave 10 related questions about vocabulary assessments conducted by Junior High School English Teacher and then shared with each respondents. The results of this study show that the teacher always use vocabulary in learning English for one semester, the learning resources they use are books, dictionaries and the internet, 80% of the teachers used multiple choice and essay types for questions about vocabulary, 70% of teachers used more than 10 test items to test vocabulary mastery in a meeting session, 80% of teachers agree that vocabulary learning can be combined with other learning materials in English, 70% of teachers always give assignments to students regarding vocabulary material, 80% of teachers use the learning media method for vocabulary learning, on average, teachers use 40% of vocabulary material in student exams. With strategies and methods used by teachers only 50% can achieve the target to add vocabulary to their students.